Effects of Iranian herbal Zofa® syrup for the management of clinical symptoms in patients with COVID-19: A randomized clinical trial - Ali Ghazvini; Amir Vahedian-azimi; Morteza Abdoli; Farshid Rahimibashar; Yunes Panahi; Thozhukat Sathyapalan; Amirhossein Sahebkar (Mashhad University of Medical Sciences, 2023)
Objective: The objective of this study was to determine the role of Iranian herbal Zofa® syrup in improving the clinical symptoms of patients with COVID-19.Materials and Methods: This randomized clinical trial was conducted on 105 patients with COVID-19. Patients were randomly assigned to the intervention (n=35) group (received 10 ml of Zofa® syrup every 8 hours/seven days plus standard treatment) or the control (n=70) group (received only standard treatment). Assessments were performed before and after treatment.Results: The groups were comparable regarding age (p=0.980), gender (p=0.584), comorbidities (p=0.318), or drug history (p=0.771). There was no difference between patients' recovery status at the time of discharge (p=0.327) or two weeks post-discharge (p=0.165) in the intervention and control groups. No patient was hospitalized to the intensive care unit (ICU) for supplemental oxygen therapy and no patient died in the intervention group. However, in the control group, three (4.5%) patients were transferred to the ICU, and two (3.03%) patients died.Conclusion: Considering the better recovery status of the patients at the time of discharge and the absence of patient deaths in the intervention group, more additional studies are needed to confirm these findings and elucidate the role of Zofa® in COVID-19.